Enforcement of Criminal Law Against Perpetrators of Criminal Acts of Attacking Vital Organs (Study of Decision Number: 59/Pid.B/2021/PN Lbh) - Suhartini, Siti Pujiastuti (Dinasti Research, 2025)
This research aims to analyze the proof of the element “intentionally” in the crime of taking the life of another person through an attack on the victim's vital organs. In cases such as murder and maltreatment causing death, the element of intent is a key element that must be proven, although it is often difficult to prove in practice. This research examines the application of jurisprudence Number 1/Yur/Pid/2018 and how this principle is applied in District Court Decision Number 59/Pid.B/2021/PN LBH. The method used is normative legal research with the approach of legislation, concepts, and cases. The results show that based on “Jurisprudence Number 1/Yur/Pid/2018” which states “The element of intentionally taking life is fulfilled if the perpetrator attacks the victim with tools, such as sharp weapons and firearms, in parts of the body where there are vital organs, such as the chest, abdomen and head”. In the verdict in criminal case number 59/Pid.B/2021/Pn Lbh, there was no unanimous consensus due to differences of opinion caused by the difficulty of proving the element of intent on the part of the Defendant, which in the end the Defendant was found legally and convincingly guilty of committing the crime of persecution.